"Body Work" in Home-Based Substance Abuse Care - Günther Kirsi (Cogitatio, 2022)
This study examines “body work” in the context of home‐based substance abuse care in Finland, which is provided to adults with intoxicant problems and needing short‐ and long‐term support in their everyday lives. This article is concerned specifically with body work, which can be defined as care work focusing directly on the bodies of others. Through a twofold analysis of 13 audio‐recorded home visits and ethnographic field notes, it examines what body work is in home‐based substance abuse care, how close body work is and how workers and clients negotiate about it. The study shows that home as a site of care has an impact on substance abuse care. The worker’s home visit settles into a tension relation between private and public even if the care is a part of weekly routine. Body work is holistic care work necessitating slight, medium,
and extreme bodily intimacy in taking care of and supporting client’s well‐being. During the home visit, worker and client negotiate the body work and its content. Worker and client communicate verbally and non‐verbally by gaze and body movements. Often the workers have to balance between disciplinary, participatory, and caring approaches to support the client living in the best possible way.